Studi Literatur tentang Konsep Tol Laut dan Dampaknya Terhadap Disparitas Harga Barang Umum di Indonesia - Upik Sri Rahayu; Eliyanti A. Mokodompit (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Indonesia, as the largest archipelagic country in the world, structurally faces acute connectivity challenges, resulting in high national logistics costs and significant price disparities between production centers in Western Indonesia and consumer regions in Eastern Indonesia. This study aims to analyze the Sea Toll Concept, a strategic maritime policy of the Indonesian Government designed to realize efficient and sustainable maritime connectivity, with the primary objective of reducing price disparities between regions. Using the Systematic Literature Review (SLR) Method and a Descriptive Qualitative approach, this study synthesizes findings from national scientific journals published between 2020 and 2025. The analysis was conducted using three theoretical frameworks: Logistics and SCM Theory, Regional Economics and Trade Theory, and Regional Development and Balance Theory. The analysis found that the Sea Toll program is strategically effective in reducing price disparities. With recorded price reductions ranging from 8% to 30% in destination areas. This success is driven by mitigating distance barriers and increasing supply stability. However, the program faces systemic constraints related to the Total Cost Concept Theory, as evidenced by statistically insignificant price changes at the retail level, indicating that front-haul savings are being absorbed by structural constraints on ground infrastructure (last-mile) and the Imperfect Market Theory. To achieve total efficiency, integrated multi-modal policies that focus on developing the back-haul economic base and addressing local market competition are required.